Experimental study on low-temperature organic Rankine cycle utilizing scroll type expander. (1st October 2015) - Chang, Jen-Chieh; Hung, Tzu-Chen; He, Ya-Ling; Zhang, Wenping
Highlights: Experimental studies of the ORC system operating with R245fa are presented. Scroll type expander was employed in the ORC system. The cycle was fueled with hot water (maximum 95.6 °C). Superheating improves isentropic efficiency of the expander. Abstract: This paper focuses on experimental performance of an open-drive scroll type expander in an organic Rankine cycle (ORC) system. The expander was an originally oil-free scroll type air compressor with a built-in volume ratio of 4.05. The cycle used HFC-245fa as working fluid, and the loop has been mixed with a moderate concentration of refrigerant oil that circulated in the cycle. The experimental results of this study are divided into two main parts: first part focuses the experimental performance on the fixed superheating at the expander inlet with respect to various pressure differences of the system and rotational speeds of the expander. Second part involves various superheating at the expander inlet which was operated at fixed rotational speed and operating pressure difference of 5 bars and 6 bars. When the cycle was operated under fixed superheating conditions, the maximum cycle efficiency, expander efficiency and power output of the expander are 9.44%, 73.1% and 2.3 kW respectively. On the other hand, when the expander is operated in various superheating conditions, the expander and cycle efficiency simultaneously increase with the increasing of superheating. In addition, this paper not only focuses on the experimental results using the current expander, but also integrates the previous experimental data with present study to identify an appropriate scroll type expander with respect to various operating pressure differences for the heat source below 100 °C.